Pengaruh Flash Sale Dan Gratis Ongkir Terhadap Impulse Buying Pada Marketplace Shopee - Galih Panjalu Pramono; I Made Luhur Adi Putra; Kiki Mulyadi (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2024)
The research was conducted on Shopee marketplace users in Banyumas Regency. The purpose of this study was to determine the influence of flash sales and free shipping on impulse buying among Shopee marketplace users in Banyumas Regency, both partially and simultaneously. The sample used consisted of the entire population or residents domiciled in Banyumas Regency, amounting to 97 individuals. The types of data utilized were primary data collected through distributing questionnaires directly to respondents and secondary data obtained from literature studies. The method employed in data analysis was multiple linear regression analysis, encompassing t-tests and f-tests after testing the data for validity, reliability, and classical assumptions. The classical assumption tests comprised multicollinearity, heteroskedasticity, and normality tests using SPSS software. The research findings indicate that flash sales do not have a significant effect, whereas free shipping significantly influences impulse buying.